ЭКОЛОГИЧЕСКИЕ ФАКТОРЫ И ПРОБЛЕМЫ СОХРАНЕНИЯ РАЗНООБРАЗИЯ РЫБ В ОЗЕРЕ ИССЫК-КУЛЬ (Eurasian Journal of Ecology, 2016)
In the article, there is given an analysis of reasons and problems resulted after human activity in Issyk-Kul Lake Basin, in particular after introduction and acclimatization of some fishes into this drainless water body. Also there are considered positive and negative consequences of any works on acclimatization, and some measures are recommended which can promote to conservation and renewal of aboriginal fish populations.